THE GIVING OF STRETCHING EXERCISE TO CHANGES IN LEVELS OF DYMENORRHES IN ADOLESCENT FEMALE CLASS VIIAT SMPN 1 PRAMBON, NGANJUK DISTRICT - Puji Astutik (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Dysmenorrhea is a menstrual disorder that is often experienced by young women, if left untreated it will interfere with learning concentration. Stretching exercise is an alternative to overcome dysmenorrhea. The purpose of this study was to determine the effect of giving stretching exercise on changes in the level of dysmenorrhea in class VII young women at SMPN 1 Prambon, Nganjuk Regency. The research design used a pre-experimental design (one group pre-test-post test design) which was carried out November 5 â€“ 18, 2022. The population consisted of 40 young women, using a purposive sampling technique to obtain a sample of 30 respondents. The independent variable of the research is the giving of stretching exercise, while the dependent variable of the research is the change in the level of dysmenorrhea. Collecting independent variable data with SOP and dependent variable with Numeric Rating Scale. Statistical test using Wilcoxon Signed Ranks with a significance level of Î± = 0.05. The results of the study before doing stretching exercises almost half experienced moderate pain as many as 12 (43%) of 30 respondents, and after doing stretching exercises almost half experienced mild pain, namely 14 (47%) of 30 respondents. The results of the Wilcoxon Signed Ranks statistical test showed Ï value = 0.014 < Î± = 0.05 so Ha was accepted, which means that there is an effect of giving stretching exercise on changes in the level of dysmenorrhea in class VII young women at SMPN 1 Prambon Nganjuk. Based on the results of the study, stretching exercise affects changes in the level of dysmenorrhea in female adolescents. This is because when doing stretching exercises the body will produce endorphins. Endorphins are produced in the brain and spinal cord. This hormone can function as a natural sedative that is produced by the brain, causing a feeling of comfort that can relieve pain.